1977
DOI: 10.1128/aac.12.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Activity of the Combinations of Gentamicin with Clindamycin or Chloramphenicol Against Species of Escherichia coli and Bacteroides fragilis

Abstract: The bactericidal activity of clindamycin, chloramphenicol, and gentamicin alone and of gentamicin plus clindamycin and gentamicin plus chloramphenicol was studied on 8 strains of Escherichia coli and 10 strains of Bacteroides fragilis isolated from clinical material. Gentamicin did not interfere with the activity of clindamycin or chloramphenicol against B. fragilis . The activity of gentamicin against E. coli was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 10 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…The authors found antagonism between chloramphenicol and the five analyzed betalactams [128]. Similarly, an antagonism was found with ceftriaxone against enteric Gram-negative rods [129] and with gentamicin against isolates of Escherichia coli and Bacteroides fragilis [133,134]. Regarding penicillin G, a synergistic bactericidal effect with chloramphenicol was observed in 17 out of 20 beta-lactamase-producing strains of S. aureus.…”
Section: Enterobacter Sppmentioning
confidence: 83%
See 2 more Smart Citations
“…The authors found antagonism between chloramphenicol and the five analyzed betalactams [128]. Similarly, an antagonism was found with ceftriaxone against enteric Gram-negative rods [129] and with gentamicin against isolates of Escherichia coli and Bacteroides fragilis [133,134]. Regarding penicillin G, a synergistic bactericidal effect with chloramphenicol was observed in 17 out of 20 beta-lactamase-producing strains of S. aureus.…”
Section: Enterobacter Sppmentioning
confidence: 83%
“…Data on the activity of chloramphenicol combinations with other antimicrobial agents (cont. [133,134] Penicillin Cellophane transfer technique 20 isolates of S. aureus…”
Section: Mycobacterium Smegmatismentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this finding, this agent has been most frequently studied in combination with other antibiotics, such as clindamycin (4,18) and spiramycin (11), which proved to be synergistic. The combination of clindamycin and gentamicin has been found to be synergistic by some (5,16) but not by all investigators (10). …”
Section: Discussionmentioning
confidence: 99%
“…(4,5,10,16). A by-product of these studies has been the discovery that some antibiotics act synergistically against B. fragilis.…”
mentioning
confidence: 99%